2011
DOI: 10.1371/journal.pone.0017718
|View full text |Cite
|
Sign up to set email alerts
|

Role of Androgen Receptor CAG Repeat Polymorphism and X-Inactivation in the Manifestation of Recurrent Spontaneous Abortions in Indian Women

Abstract: The aim of the present study was to investigate the role of CAG repeat polymorphism and X-chromosome Inactivation (XCI) pattern in Recurrent Spontaneous Abortions among Indian women which has not been hitherto explored. 117 RSA cases and 224 Controls were included in the study. Cases were recruited from two different hospitals - Lakshmi Fertility Clinic, Nellore and Fernandez Maternity Hospital, Hyderabad. Controls were roughly matched for age, ethnicity and socioeconomic status. The CAG repeats of the Androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…This may lead to better management options and eventually prevention strategies for obesity and possibly lessen infertility. Androgen responsivity secondary to AR gene CAG repeat length has a multi-level influence on human reproduction and fertility through effects on male testicular development and spermatogenesis [27,28] and female pregnancy outcomes [29]. Our study further reports male stature and female weight as androgen responsive modulatory variables with potential influence on fertility.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This may lead to better management options and eventually prevention strategies for obesity and possibly lessen infertility. Androgen responsivity secondary to AR gene CAG repeat length has a multi-level influence on human reproduction and fertility through effects on male testicular development and spermatogenesis [27,28] and female pregnancy outcomes [29]. Our study further reports male stature and female weight as androgen responsive modulatory variables with potential influence on fertility.…”
Section: Discussionsupporting
confidence: 54%
“…Diminished in vivo androgenicity in males leads to decreased spermatogenesis and smaller seminal vesicles [24][25][26][27] thereby impacting fertility and human reproduction [28]. AR gene CAG repeat lengths above 21 correlate with poor pregnancy outcomes in females and recurrent spontaneous abortions [29]. Androgen receptor gene CAG repeat length is also associated with ovarian reserve and may play a role in ovulation but the natural ovarian aging process does not appear to affect ovarian response to gonadotropins [30].…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies showed an increased highly SXCI in patients who had experienced RSA compared with the control group (Bagislar et al, 2006;Beever et al, 2003;Dasoula et al, 2008;Hogge et al, 2007;Kuo et al, 2008;Sullivan et al, 2003;Uehara et al, 2001), whereas the other five reported lower prevalence of SXCI in cases of RSA than in normal females (Aruna et al, 2011;Kaare et al, 2008;Kim et al, 2004;Pasquier et al, 2007;Warburton et al, 2009). Random effect model was used for the heterogeneity test showed P = 0.004, and results of meta-analyses result showed no significant difference in the incidence of SXCI in cases of RSA and controls (OR = 1.58 [0.83 to 3.01]) (Figure 2).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Full manuscripts were obtained for the remaining 19 articles for detailed evaluation; after scrutiny, four articles were excluded as they were reviews, three studies (Lanasa et al, 1999(Lanasa et al, , 2001Sangha et al, 1999) were excluded for the duplication of population. Twelve case-control studies (Aruna et al, 2011;Bagislar et al, 2006;Beever et al, 2003;Dasoula et al, 2008;Hogge et al, 2007;Kaare et al, 2008;Kim et al, 2004;Kuo et al, 2008;Pasquier et al, 2007;Sullivan et al, 2003;Uehara et al, 2001;Warburton et al, 2009) were, therefore, included in the meta-analysis, all in English and published as full text, with characteristics presented in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The expansion of CAG repeats, coding for a polyglutamine (polyQ) tract in the N-terminal domain, leads to an increased transactivation function (21). Several clinical conditions had been shown to be associated with the length of CAG repeats in the AR gene (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%